2013
DOI: 10.1038/ismej.2013.197
|View full text |Cite
|
Sign up to set email alerts
|

Ecological succession among iron-oxidizing bacteria

Abstract: Despite over 125 years of study, the factors that dictate species dominance in neutrophilic iron-oxidizing bacterial (FeOB) communities remain unknown. In a freshwater wetland, we documented a clear ecological succession coupled with niche separation between the helical stalk-forming Gallionellales (for example, Gallionella ferruginea) and tubular sheath-forming Leptothrix ochracea. Changes in the iron-seep community were documented using microscopy and cultivation-independent methods. Quantification of Fe-oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 49 publications
7
90
0
Order By: Relevance
“…Somewhat surprisingly, the overall relative abundance of Gallionellales and Leptothrix spp. ranged from 3 to 10%, whereas in temperate iron seeps, these groups may account for between 25 and 50% of the total population (18,21,22). It is not clear why the abundances of known FeOB are reduced in these tundra iron mats.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Somewhat surprisingly, the overall relative abundance of Gallionellales and Leptothrix spp. ranged from 3 to 10%, whereas in temperate iron seeps, these groups may account for between 25 and 50% of the total population (18,21,22). It is not clear why the abundances of known FeOB are reduced in these tundra iron mats.…”
Section: Discussionmentioning
confidence: 95%
“…5). The specific reasons for clustering of the TFS samples with the early successional community in Maine are not understood; however, the average temperature was 11°C for the early season community in Maine, similar to the temperature for TFS sites, while later in the season, the temperature in Maine rose to 15 to 18°C (18). A more complete analysis of the microbiome (13 sites and 40 samples) of microbial iron mats from Maine, Virginia, Texas, and Wyoming and in Denmark found that TFS iron mats cluster much more closely to these other circumneutral terrestrial sites than they do to iron-oxidizing communities from acidic (pH Ͻ4) or marine environments (J. J. Scott and D. Emerson, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…These processes commonly occur simultaneously upon mixing of iron-rich, anoxic groundwater with oxygen-rich surface water (Druschel et al 2008). Iron biomineral formation from microbially mediated processes has been identified in diverse aqueous environments, including acid mine drainage sites (Colmer et al 1950;Baker et al 2009;Johnson and Hallberg 2015), hydrothermal vents (Emerson et al 1999;Peng et al 2011;Toner et al 2012), and circumneutral pH surface waters (Emerson and Moyer 1997;Duckworth et al 2009;Emerson et al 2010;Fleming et al 2014). In many circumneutral pH waters, abiotic oxidation is in direct competition with neutrophilic iron oxidizing bacteria (FeOB), organisms that exist at oxic-anoxic interfaces and have metabolic capabilities that promote rapid iron oxidation (Druschel et al 2008).…”
mentioning
confidence: 99%
“…In many circumneutral pH waters, abiotic oxidation is in direct competition with neutrophilic iron oxidizing bacteria (FeOB), organisms that exist at oxic-anoxic interfaces and have metabolic capabilities that promote rapid iron oxidation (Druschel et al 2008). Multiple neutrophilic, microaerophilic FeOB, such as Leptothrix, Gallionella, and Sideroxydans, have been identified and studied to understand biotic-abiotic interactions in diverse environments (Duckworth et al 2009;Fleming et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation